ANALISIS PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Penjualan di PT. Perindustrian Bapak Djenggot Bergas, Semarang) - Hanantoko, Destu Aji; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2017)
Human Resources is one factor that is vital as a determinant of the success of the company. The Company's success itself is usually determined from the performance of its employees. From the results of the pre-survey known phenomenon that occurs in the company is a decrease in employee performance. On the other hand the discovery of Research Gap from previous studies on the influence of work motivation, leadership and organizational culture on employee performance. This is the background to do the research.This study uses the work motivation, leadership and organizational culture as an independent variable, and employee performance as the dependent variable. The population of this research is a sales employee of PT. Industry Mr. Djenggot Bergas Semarang. The sampling technique used is sampling saturated, with a sample of 64 people. The data obtained has been tested reliability and invalidity using validity and reliability. The method used in this research is multiple linear regression analysis.Based on the results of multiple linear regression analysis showed that there is a positive and significant influence of work motivation, leadership and organizational culture on employee performance. Of the coefficient of determination shows that motivation, leadership and organizational culture influence on employee performance of sales PT. Industry Mr. Djenggot Bergas Semarang 23.4%. While the remaining 76.6% is explained by other variables that are not described in this study.